The number of FoxP3+ cells in transbronchial lung allograft biopsies does not predict bronchiolitis obliterans syndrome within the first five years after transplantation. (9th March 2015) - Krustrup, Dorrit; Iversen, Martin; Martinussen, Torben; Schultz, Hans Henrik L.; Andersen, Claus B.
Abstract Background An important limitation to the success of lung transplantation is the development of bronchiolitis obliterans syndrome (BOS). It has been hypothesized that regulatory T lymphocytes (Tregs) are related to the risk of BOS. We aim to evaluate whether the number of forkhead box P3 (FoxP3+) cells/mm2 in lung allograft biopsies is a predictor of long‐term outcome. Materials and Methods A total of 58 consecutive lung transplant patients were included in the study. For 233 routine surveillance biopsy samples, the numbers of FoxP3+ cells/mm2 were assessed by immunohistochemical staining with antibodies against FoxP3. BOS scores were calculated for the first five yr after transplantation. Results We determined that acute rejection was related to the time elapsed from transplantation to BOS with hazard ratios of 3.18 (p = 0.02) and 3.73 (p = 0.04) when comparing the levels of acute rejection grade 1 and grade 2/3, respectively, to no rejection. According to a Cox regression analysis, the number of FoxP3+ cells/mm2 was not predictive of time to BOS. Discussion and Conclusions Our data indicate that the number of FoxP3+ cells in the lung allograft did not correlate with BOS‐free survival time. Previous studies have been contradictory and included different time points. Our findings emphasize the importance of including a time factor.